2015
DOI: 10.1371/journal.pone.0129296
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Cigarette Topography in the Natural Environment

Abstract: This paper presents the results of a clinical, observational, descriptive study to quantify the use patterns of electronic cigarette users in their natural environment. Previously published work regarding puff topography has been widely indirect in nature, and qualitative rather than quantitative, with the exception of three studies conducted in a laboratory environment for limited amounts of time. The current study quantifies the variation in puffing behaviors among users as well as the variation for a given … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
121
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(132 citation statements)
references
References 25 publications
9
121
1
Order By: Relevance
“…Despite methodological differences, puff durations under high and low nicotine conditions observed here are similar to those previously reported in experienced users using newer generation devices (Farsalinos et al, 2014;Hua et al, 2013) but longer than those reported for cartomiser (first-generation) devices (Behar, Hua, & Talbot, 2015) and tobacco cigarettes (Hua et al, 2013). Our study was conducted in a controlled laboratory environment which may not reflect real-world puffing behaviour (Robinson, Hensel, Morabito & Roundtree 2015) possibly over-estimating puffing. Indeed, the self-reported daily mL usually consumed (mean: 4.09 ± 1.79l; see Table 1) supports this notion, although the 12 h abstinence period may have also contributed to the intense puffing patterns as participants strive to raise fallen nicotine levels.…”
Section: Discussionsupporting
confidence: 78%
“…Despite methodological differences, puff durations under high and low nicotine conditions observed here are similar to those previously reported in experienced users using newer generation devices (Farsalinos et al, 2014;Hua et al, 2013) but longer than those reported for cartomiser (first-generation) devices (Behar, Hua, & Talbot, 2015) and tobacco cigarettes (Hua et al, 2013). Our study was conducted in a controlled laboratory environment which may not reflect real-world puffing behaviour (Robinson, Hensel, Morabito & Roundtree 2015) possibly over-estimating puffing. Indeed, the self-reported daily mL usually consumed (mean: 4.09 ± 1.79l; see Table 1) supports this notion, although the 12 h abstinence period may have also contributed to the intense puffing patterns as participants strive to raise fallen nicotine levels.…”
Section: Discussionsupporting
confidence: 78%
“…Platelets play an integral role in maintaining hemostasis, and changes in their counts have been linked to mortality and CVD development 24. Furthermore, while the effect of “smoke” on platelet count remains controversial, with studies showing it to be increased51 or unaffected,52, 53 we sought to examine whether e‐cigarettes would produce any effects under our experimental conditions.…”
Section: Resultsmentioning
confidence: 99%
“…A 15‐minute break between the 2 exposure sessions was given so that the animals could access fresh air, food, and water. The puff duration was 3 seconds, puff interval 1 minute, and the puff volume was 50 mL, all of which mimics real‐life exposure scenarios 24, 25, 26, 27, 28, 29, 30, 31, 32, 33. As for the controls or control mice, they were matched in terms of age and sex (ie, 10‐week‐old males), and were exposed to clean air.…”
Section: Methodsmentioning
confidence: 99%
“…In order to capture these irregular types of use, data collection methods adopting real-world settings have been reported and discussed, such as mobile e-cigarettes or Ecological Momentary Assessment. 16,17 Initial Ecological Momentary Assessment data have revealed an under-reporting of the number of e-cigarette puffs relative to data from Bluetooth-enabled e-cigarettes. 16 One thing that is apparent from the focus groups is that much of the behavior of today's vapers is not consciously tracked.…”
Section: Discussionmentioning
confidence: 99%